Neuromyelitis optica and neuromyelitis optica spectrum disorders: the evaluation of 86 patients followed by Istanbul Bilim University - Altunrende, Burcu; Tavlı, Ahmet Mithat; Altınkaya, Ayça; Topçular, Barış; Kocarslan, Meryem; Server, Sadık; Fırtına, Sinem; Yenice, Sedef; Akman Demir, Gülsen (Sage Publications Ltd., 2014)
[Abstract Not Available]
Joint ACTRIMS-ECTRIMS Meeting -- SEP 10-13, 2014 -- Boston, MA
WOS: 000354441300815
Keywords: Neuromyelitis Optica; Spectrum Disorders; Istanbul Bilim University